Editor's Choice – Decrease in Mortality from Abdominal Aortic Aneurysms (2001 to 2015): Is it Decreasing Even Faster?. (June 2021) - Png, C.Y. Maximilian; Wu, Jingting; Tang, Tjun Y.; Png, Ivan P.L.; Sheng, Tay J.; Choke, Edward
Abstract : Objective: The early twenty first century witnessed a decrease in mortality from abdominal aortic aneurysms (AAA), which was associated with variations in the prevalence of cardiovascular risk factors. This study investigated whether these trends continued into the second decade of the twenty first century. Methods: Information on AAA mortality (2001 − 2015) using International Classification of Diseases codes was extracted from the World Health Organization (WHO) mortality database. Data on risk factors were extracted from the Institute of Health Metrics and Evaluation and WHO InfoBase, and data on population from the World Development Indicators database. Regression analysis of temporal trends in cardiovascular risk factors was done independently for correlations with AAA mortality trends. Results: Seventeen countries across four continents met the inclusion criteria (Australasia, two; Europe, 11; North America, two; Asia, two). Male AAA mortality decreased in 13 countries (population weighted average: −2.84%), while female AAA mortality decreased in 11 countries (population weighted average: −1.64%). The decrease in AAA mortality was seen in both younger (< 65 years) and older (> 65 years) patients. The decrease in AAA mortality was more marked in the second decade of the twenty first century (2011 – 2015) compared with the first decade (2001 – 2005 and 2006 – 2010). Trends in AAA mortality positively correlated with smoking (males: p  = .03X, females: p  = .001) and hypertension (males: p  = .001, females: p  = .01X). Conversely, AAA mortality negatively correlated with obesity (males: p  = .001, females: p  = .001), while there was no significant correlation with diabetes. Conclusion: AAA mortality has continued to decline and seems to have declined at an even faster rate in the second decade of the twenty first century, albeit with heterogeneity among countries. These variations are multifactorial in origin but further efforts targeting smoking cessation and blood pressure control will probably contribute to continued reductions in AAA mortality.